Avidity of pertussis toxin antibodies following vaccination with genetically versus chemically detoxified pertussis toxin-containing vaccines during pregnancy - Abu-Raya, Bahaa; Del Giudice, Giuseppe; van den Biggelaar, Anita H. J.; Tang, Yuxiao; Bhat, Niranjan; Pham, Hong Thai; Wijagkanalan, Wassana (Frontiers in Immunology, 2025)
BackgroundBoth the quantity and quality of circulating anti-pertussis toxin antibodies are important for protection against severe pertussis. We compared the avidity of PT-IgG antibodies in pregnant women and their infants following vaccination during pregnancy with pertussis vaccines containing genetically-detoxified pertussis toxin (PTgen) or chemically-detoxified PT (PTchem).MethodsWe analyzed serum samples collected earlier from pregnant women (at delivery) and their infants (at birth and 2 months of age) participating in a clinical trial where pregnant women had been vaccinated during pregnancy with recombinant acellular pertussis vaccine containing 1 µg PTgen (standalone, ap1gen, [n=37], or combined to tetanus and diphtheria, Tdap1gen [n=34]), 2 µg PTgen (Tdap2gen, n=35), or 5 µg PTgen (TdaP5gen, n=34), or acellular pertussis vaccine containing 8 µg PTchem (Tdap8chem, n=35). Avidity was assessed by adding increasing concentrations (0.25, 0.5, 1, 1.5, 2, and 3 M) of NH4SCN as a bond-breaking agent and measuring PT-IgG levels by ELISA.FindingsCompared with Tdap8chem, TdaP5gen vaccination was associated with significantly higher total absolute avidity (p<0.001) and medium-high to very-high avidity PT-IgG levels (p≤0.02) in mothers at delivery, infants at birth and infants at 2 months of age. Avidity was comparable to Tdap8chem after vaccination with the low-dose PTgen formulations (ap1gen, Tdap1gen or Tdap2gen). There were no differences for vaccination during the 2nd or 3rd trimester of pregnancy.InterpretationCompared with chemically detoxified vaccines, vaccination during pregnancy with recombinant genetically detoxified acellular pertussis vaccine at lower PT concentration provides infants with at least similar or higher quality PT-IgG antibodies. Consequently, recombinant pertussis vaccines may offer comparable or better protection against pertussis.